Correlation of systemic immune-inflammation index and moderate/major depression in patients with depressive disorders: a large sample cross-sectional study - Cui, Shu; Li, Juanjuan; Liu, Yun; Yao, Gaofeng; Wu, Yanhai; Liu, Zhiwei; Sun, Liang; Sun, Longlong; Liu, Huanzhong (Frontiers in Psychiatry, 2023)
Objective To evaluate the clinical value of systemic immune-inflammation index (SII) based on peripheral blood neutrophil, lymphocyte, and platelet count in evaluating the subtype and severity of depression in patients with depressive disorder. Methods This retrospective cohort study was conducted in the Third People's Hospital of Fuyang City from January 1, 2020 to December 31, 2022. The data included sociodemographic information at admission, clinical data, discharge diagnosis and inflammatory markers. Patients were divided into low SII group and high SII group according to the optimal threshold of SII determined by receiver operating characteristic curve (ROC curve). Binary Logistic regression was used to analyze the correlation between moderate/major depression and SII level. Results Compared to the low SII group, the high SII group had a higher age level (χ2=7.663, P=0.006), more smokers (χ2=9.458, P=0.002), more moderate/major depression patients (χ2=45.645, P < 0.001), and a higher proportion of patients with accompanying somatic symptoms (χ2=14.867, P < 0.001). In the final logistic regression model, after controlling for confounding factors, SII at admission was significantly associated with moderate/major depression (β =1.285, P＜0.001; odds ratio [95% confidence intervals] = 3.614 [2.693-4.850]). Patients with high SII scores were 3.614 times more likely to have moderate/severe depression than those with low SII scores. We propose a cut-off value of SII =540.78 (sensitivity = 36.4% and specificity = 80.3%) according to the maximum Youden index. Conclusions Our research indicates that SII may be a useful, repeatable, convenient, and affordable index to identify moderate/major depression in depressive disorder.